HIV infection modifies the relationship between distance to a health facility and treatment success rate for tuberculosis in rural eastern Uganda - Olupot, Ben; Adrawa, Norbert; Bajunirwe, Francis; Izudi, Jonathan (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases, 2020)
Rationale: Distance from residence to a health facility especially in rural areas presents a physical barrier and may influence tuberculosis (TB) treatment outcomes. Objectives: We examined the association between distance from residence to a health facility and TB treatment outcomes namely treatment success rate (TSR) and mortality, and whether HIV influences this relationship among people with TB in Kumi district in rural eastern Uganda. Methods: In this cross-sectional design, we abstracted data from TB unit registers across four large health facilities. Travel of ≥5 km to a health facility was considered a long distance. The primary outcome was TSR and the secondary was mortality. We performed a generalized linear model with Poisson distribution with a log-link and robust standard errors to determine the association between distance and the study outcomes adjusting for potential confounders. We report the adjusted risk ratio (aRR) and 95% confidence interval (CI). Measurement and results: Of 611 participants studied, 484 (79.2%) were successfully treated, 18 (2.9%) died, and 359 (58.7%) travelled a long distance to access TB treatment. Long-distance was significantly associated with lower TSR (aRR, 0.93; 95% CI, 0.89–0.96). Further analysis showed that longer distance was associated with lower TSR among HIV positive persons with TB (aRR, 0.83; 95% CI, 0.72–0.96), but not among HIV negative persons with TB (aRR, 0.94; 95% CI, 0.85–1.03). Although it was not significant, longer distance showed a tendency towards worse mortality among HIV positive people with TB (aRR, 2.78; 95% CI, 0.80–9.66), but not among HIV negative people with HIV (aRR, 0.21; 0.03–1.74). Conclusions: A majority of people with TB travel long distances to access treatment. Long distances are associated with lower TSR and higher mortality and affect people with TB who are HIV positive but not HIV negative. Interventions should focus on improving access to treatment for people with TB who travel long distances.
Keywords: Drug susceptible pulmonary tuberculosis; Treatment success rate; Mortality; HIV